2015
DOI: 10.1890/es14-00353.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships for estimating N2 fixation in legumes: incidence for N balance of legume‐based cropping systems in Europe

Abstract: Citation: Anglade, J., G. Billen, and J. Garnier. 2015. Relationships for estimating N 2 fixation in legumes: incidence for N balance of legume-based cropping systems in Europe. Ecosphere 6(3):37. http://dx.doi.org/10.1890/ES14-00353.1Abstract. Management of nitrogen (N) inputs into agricultural systems is of increasing interest due to the intensive use of synthetic fertilizers in modern cash crop systems, which has caused considerable environmental damage, including nitrate contamination of surface and ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(119 citation statements)
references
References 145 publications
6
108
2
3
Order By: Relevance
“…Furthermore, we lack hard evidence that BNF itself produces 'excess N'. Instead, and provided crop legumes are not augmented with INF, there is every prospect of maintaining balanced N budgets when crop legumes are used as both a source of grain and N. Recent detailed analysis of the N balance of legume-based cropping systems in Europe [45] showed that for a typical legume-cereal rotation, there was little N (a few kg ha…”
Section: Biological Nitrogen Fixation and Nitrogen Use Efficiency Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we lack hard evidence that BNF itself produces 'excess N'. Instead, and provided crop legumes are not augmented with INF, there is every prospect of maintaining balanced N budgets when crop legumes are used as both a source of grain and N. Recent detailed analysis of the N balance of legume-based cropping systems in Europe [45] showed that for a typical legume-cereal rotation, there was little N (a few kg ha…”
Section: Biological Nitrogen Fixation and Nitrogen Use Efficiency Of mentioning
confidence: 99%
“…Legumes are frequently noted as being 'drought sensitive', to the extent that farmers can be wary of growing them under dry seasonal conditions. A strong, N-based response to drought (accumulation of amino acids) was interpreted [45] as being a potential mechanism to account for slowing rates of N fixation for the perennial legume Medicago. For grain legumes, a very similar response was noted for Cicer [46], while Phaseolus accumulated ureides in foliage (but not nodules) under drought conditions that also inhibited BNF [47].…”
mentioning
confidence: 99%
“…Several authors reported a positive response of switchgrass yields to increasing nitrogen (N) fertilisation levels (Gurezky et al, 2010;Nassi o Di Nasso et al, 2015). Nevertheless, nitrogen distribution associated to grass cultivation may increase the risk of eutrophication and directly and indirectly cause GHG emissions (Anglade et al, 2015). To cope with this problem, the use of a legume as intercropping species appears to be an environmental friendly option to increase N use efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…For the 2014 and 2015 calculation, estimates of pasture BNF were updated using a robust pasture survey, legume sample analysis (using an elemental analyzer) and equations relating legume N content to rates of N fixation (Gorksy 2016, Anglade et al 2015). The pasture survey included sampling every meter along three 50-m transects (locations were determined using 3 randomly selected points in each field and a random direction).…”
Section: Farm N Budgetmentioning
confidence: 99%
“…Legume samples were collected (three per field), sorted (leaf materials, stem, roots), dried (at 60° for 24 hours or until a constant mass was reached), ground, and analyzed to estimate N content. Fixation was estimated as a function of stem N content (Anglade et al 2015). See Gorsky (2016) for full details.…”
Section: Farm N Budgetmentioning
confidence: 99%